Does celebrity involvement in public health campaigns deliver long term benefit? No. (25th September 2012) - Rayner, Geof
Abstract : Simon Chapman (doi:10.1136/bmj.e6364 ) thinks that the extra publicity that celebrities provide can help promote public health, but Geof Rayner is worried about the insidious influences of celebrity